Napoli da capitale a periferia: Archeologia e mercato antiquario in Campania nella seconda metà dell'Ottocento Naples, from Center to Periphery: Archeology and Antiquarian Market in Campania during the Second Half of 19th Century. - Italo Iasiello (Clio: Saggi di scienze storiche, archeologiche e storico-artistiche, 2017)
During the 17th century antiquities of Campania received international attention thanks to the cultural politics of the Bourbon monarchy. The archaeological discoveries were considered part of the political and military success of the King of Naples. After the reunification of Italy, Naples lost its central role as heart of the antiquities collecting and trade as consequence of the marginalization of Naples as economic and political capital of a Kingdom. This process influenced the sectors archaeology, collecting and antiquity market that traditionally reflected the self-representation of the cultural and political élite. This book focuses on the social history of Neapolitan archaeology, that between the 19th and the beginning of the 20th century was strictly connected with the antiquarian market. The research analyses cultural, socio-political and institutional transformations that determinated the promulgation of a specific legislation that limited the exportation of antiquities with the aim to protect the national interest on Cultural Heritage.